2013
DOI: 10.5430/jnep.v3n11p172
|View full text |Cite
|
Sign up to set email alerts
|

Cultural diversity: A qualitative study on Saudi Arabian women's experience and perception of maternal health services

Abstract: Background: The Saudi Arabian healthcare system is mainly staffed by Non-Saudi health professionals who are recruited from all over the world. At times, inadequate cultural awareness by health professionals can render their caring for Saudi patients inadequate and thus more challenging for the women. When nurses and patients belong to different cultures, culture-based misunderstandings can influence their relationships and interactions adversely. The aim is to describe the experiences of women who were admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The patients also had difficulty in understanding the English language, so the nurse educators/clinical instructors could not discuss sexuality or birth processes in detail in front of the patient, while coaching the nursing students. This is consistent with the study by Karout et al (2013) on Saudi Arabian women"s experience and perception of maternal health services, that the biggest problem discussed by most women was that of linguistic diversity; not only the difference between the English and Arabic languages but extending to the accents of non-English speakers such as Indians, Filipinos and Pakistanis. In addition, the study conducted by Albagawi (2014) on examining barriers and facilitators to effective nurse-patient communication within the Saudi Arabian cultural context found that effective communication was not achieved because of many complex and overlapping personal, professional and organizational factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The patients also had difficulty in understanding the English language, so the nurse educators/clinical instructors could not discuss sexuality or birth processes in detail in front of the patient, while coaching the nursing students. This is consistent with the study by Karout et al (2013) on Saudi Arabian women"s experience and perception of maternal health services, that the biggest problem discussed by most women was that of linguistic diversity; not only the difference between the English and Arabic languages but extending to the accents of non-English speakers such as Indians, Filipinos and Pakistanis. In addition, the study conducted by Albagawi (2014) on examining barriers and facilitators to effective nurse-patient communication within the Saudi Arabian cultural context found that effective communication was not achieved because of many complex and overlapping personal, professional and organizational factors.…”
Section: Discussionsupporting
confidence: 90%
“…Being conservative, they can be embarrassed by questions on their sexual relationships and other personal matters. Karout et al (2013) found in their study of Saudi Arabian women"s experiences and perception of maternal health services that "the presence of non-Muslim service providers did not satisfy them because they believed that Muslim service providers will not look at their uncovered bodies especially their genitalia unless there is a need for that, and they will be conscious uncovering themselves". Thus, the Clinical Instructors found it difficult to create scenarios for the students to experience and participate in the learning process because of the patient"s culture.…”
Section: Cultural Domainmentioning
confidence: 99%
“…Even though KSA follows a conservative approach to Islam, discussion of married women’s sexual behaviour is acceptable within a medical context, so participation in research is not compromised in this population. For example, a study on Saudi Arabian women’s experiences with maternal health services elicited very intimate comments from Saudi women about their pregnancy and birthing process [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five percent of respondents indicated that nurses' nationality during patient-nurse communication has an effect. Research by Karout et al (2013) showed that Saudi patients perceived foreign female nurses (especially Filipinos and Indians) as maids or housekeepers. Almutairi et al (2015) found that Filipino nurses experienced a lack of respect from Saudi nationals.…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that cultural diversity and linguistic barriers have a negative effect on expatriate nurses' patient care experiences. A study by Karout et al (2013) determined that clients faced cultural communication difficulties in some cases. These difficulties could lead to misunderstandings that could then result in diminished care provided by the nurses.…”
Section: Literature Reviewmentioning
confidence: 99%